The psychological burden of waiting for procedures and patient‐centred strategies that could support the mental health of wait‐listed patients and caregivers during the COVID‐19 pandemic: A scoping review - Anna R. Gagliardi; Cindy Y. Y. Yip; Jonathan Irish; Frances C. Wright; Barry Rubin; Heather Ross; Robin Green; Susan Abbey; Mary Pat McAndrews; Donna E. Stewart (Wiley, 2021)
Abstract Background Waiting for procedures delayed by COVID‐19 may cause anxiety and related adverse consequences. Objective To synthesize research on the mental health impact of waiting and patient‐centred mitigation strategies that could be applied in the COVID‐19 context. Methods Using a scoping review approach, we searched 9 databases for studies on waiting lists and mental health and reported study characteristics, impacts and intervention attributes and outcomes. Results We included 51 studies that focussed on organ transplant (60.8%), surgery (21.6%) or cancer management (13.7%). Most patients and caregivers reported anxiety, depression and poor quality of life, which deteriorated with increasing wait time. The impact of waiting on mental health was greater among women and new immigrants, and those of younger age, lower socio‐economic status, or with less‐positive coping ability. Six studies evaluated educational strategies to develop coping skills: 2 reduced depression (2 did not), 1 reduced anxiety (2 did not) and 2 improved quality of life (2 did not). In contrast, patients desired acknowledgement of concerns, peer support, and periodic communication about wait‐list position, prioritization criteria and anticipated procedure date. Conclusions Findings revealed patient‐centred strategies to alleviate the mental health impact of waiting for procedures. Ongoing research should explore how to optimize the impact of those strategies for diverse patients and caregivers, particularly in the COVID‐19 context. Patient or Public Contribution Six patients and four caregivers waiting for COVID‐19‐delayed procedures helped to establish eligibility criteria, plan data extraction and review a draft and final report.